1992
DOI: 10.1177/004947559202200306
|View full text |Cite
|
Sign up to set email alerts
|

Podoconiosis (Endemic Non-Filarial Elephantiasis) in Two Resettlement Schemes in Western Ethiopia

Abstract: In a population-based study of podoconiosis in two resettlement schemes in western Ethiopia, we found that 5% of 194 settlers and 9% of 222 indigenous people were affected. Prevalence rates were generally higher in males than females and increased with age, indicating sex differences in occupationally linked trauma to the feet and the cumulative effect of long-term exposure to volcanic soils. Persons wearing shoes had significantly lower rates than those usually walking barefoot. Suggestions are made for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 1 publication
4
34
2
1
Order By: Relevance
“…It is also higher than the prevalence documented in Burundi (1.0%) and in Rwanda (0.6%) in the 1970s [14]. More recent studies included in the current analysis have indicated prevalences of 5.5% in Wolaita, southern Ethiopia [16], 5.4% in Ocholo [25], southwestern Ethiopia, 7.0% in Pawe [24], 7.5% in Gera and Didessa [21] and 5.2% in Gulisso [17], western Ethiopia, and 7.4% in central Ethiopia [18]. Absence of information from Addis Ababa, Afar and Somali regions and the diagnostic methods used reduces the precision of the estimate.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It is also higher than the prevalence documented in Burundi (1.0%) and in Rwanda (0.6%) in the 1970s [14]. More recent studies included in the current analysis have indicated prevalences of 5.5% in Wolaita, southern Ethiopia [16], 5.4% in Ocholo [25], southwestern Ethiopia, 7.0% in Pawe [24], 7.5% in Gera and Didessa [21] and 5.2% in Gulisso [17], western Ethiopia, and 7.4% in central Ethiopia [18]. Absence of information from Addis Ababa, Afar and Somali regions and the diagnostic methods used reduces the precision of the estimate.…”
Section: Discussionmentioning
confidence: 59%
“…Without doubt, podoconiosis is one of the neglected tropical diseases (NTDs) with the greatest potential for elimination as a public health problem [20], [21]: it is preventable if shoes are consistently worn, and early stages can be successfully treated using a simple lymphoedema regimen [22]. While one million people are estimated to be affected with podoconiosis in Ethiopia [7], and a further 11 million to be at risk [23], control efforts are hampered by a lack of information on geographical distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An epidemiological study in resettlement schemes of west Ethiopia showed that the prevalence of podoconiosis is higher in indigenous (9%) people than in settlers (5%). People from non-endemic areas develop disease on average 9 years after being moved to an endemic area [21]. Apart from this, there are no recent studies on podoconiosis in west Ethiopia in general and in West Wollega zone in particular where podoconiosis is common.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to quartz, several papers hypothesize that the disease is linked to the presence of clay minerals ([7]), organic matter or elevated levels of Zr and Be ([8]) in the soils. Price ([4]) found inorganic ‘microparticles’ (described as being 0.5–2 μm in diameter, and mostly silicates) in the lymphatic tissues in both patients with and without podoconiosis, a statistically significant difference was observed in the form of the phyllosilicate within the lymph tissues of podoconiosis patients by analysing the elemental ratio of Al/Si from the particles.…”
Section: Introductionmentioning
confidence: 99%